Asymmetric Vinylogous Mukaiyama‐Mannich Reactions of Heterocyclic Siloxy Dienes with Ellman's Fluorinated Aldimines. Issue 16 (2nd July 2019) - Fustero, Santos; Rodenes, Miriam; Román, Raquel; Sedgwick, Daniel M.; Aguado, José Enrique; Soloshonok, Vadim A.; Han, Jianlin; Mei, Haibo; Medio‐Simon, Mercedes; Barrio, Pablo
Abstract: Vinylogous Mukaiyama Mannich reactions of furan and pyrrole based dienoxy silanes with α‐fluoroalkyl sulfinyl imines provide a powerful synthetic access to a variety of amino fluoroalkyl γ‐butenolide‐type and butyrolactam frameworks with high regio‐ and diastereoselectivity. Anti ‐configured adducts were obtained in all cases, independent of the nature of the heteroatom ( O or N ) present in the dienoxy silane. The absolute configuration of the adducts prepared was unequivocally established by X‐ray crystallographic analysis. It is noteworthy that the introduction of substituents at the γ‐position of the heterocyclic partner allows the generation of adducts bearing chiral quaternary centers. Abstract :